Transversal competencies of the clinical tutor of Nursing specializations: results of self-assessment - Montero-Díaz, Rodrigo; González-Juárez, Graciela; Ponce-Gómez, Gandhy (Horizonte Sanitario, 2024)
Objective: Analyze the transversal competencies of clinical tutors through diagnostic self-assessment to identify strengths and areas of opportunity in clinical tutoring. Material and methods: This is a quantitative, descriptive and cross-sectional study. The sample consisted of 95 clinical tutors hired to teach academic activities related to clinical practice in the specializations and who were willing to participate. A self assessment scale was designed that contains three dimensions and subdimensions of transversal competence and was validated by expert judging and a pilot study. It was applied through the Google Forms platform. The total variable was calculated and the corresponding percentages were obtained. Results: A differentiated diagnosis was made in strengths and areas of opportunity in the transversal competencies of the clinical tutor. In general, the self-assessment demonstrates that high percentages in the dimensions considered with not significant variations in these. Conclusions: The transversal competencies of the clinical tutor demand differentiated training to achieve a profile that contributes to the development of transversal competencies such as the ability to design learning scenarios, specialized care and the ability to evaluate learning in real practice scenarios. Keywords: Mentor; Preceptorship, Tutor; Competency-based education.